The Transformation of the System of Leasing Relations in the Real Economy Sector - Konstantinovna Ulibina, Lubov; Alekseevna Okorokova, Olga; Sergeevich Lukashov, Vladimir; Gennadevich Rusetskiy, Mikhail; Vasilievna Blizno, Liliya (International Journal of Engineering and Technology, 2018)
The article presents the analysis of the leasing mechanism as one of the main ways to improve technical and technological processes of various sectors of economy of the country. In the conditions of economic crisis and stagnation in economy the leasing instrument can positively affect the investment demand and the economy of a separate region and of the country in general. The increasing demand for leasing and its wide distribution in all branches will contribute to increasing their technical equipment, improving technological processes which could enable to overcome disproportion in the development of different of branches of economy of the country. The perspectives of the development of the leasing market in the Russian Federation will depend on the formation of consumer demand and on the value of such services; such consumer demand will timely meet all macroeconomic needs. The main factors of preserving demand for leasing in the conditions of economic and political instability must include the development of leasing relations and the state support of the leasing instrument by means of its subsidising, the high level of depreciation of fixed assets and the necessity to modernise them.Â Â